Regional-Scale Ozone Deposition to North-East Atlantic Waters - L. Coleman; S. Varghese; O. P. Tripathi; S. G. Jennings; C. D. O'Dowd (Advances in Meteorology)
A regional climate model is used to evaluate dry deposition of ozone over the North East Atlantic. Results are presented for a deposition scheme accounting for turbulent and chemical enhancement of oceanic ozone deposition and a second non-chemical, parameterised gaseous dry deposition scheme. The first deposition scheme was constrained to account for sea-surface ozone-iodide reactions and the sensitivity of modelled ozone concentrations to oceanic iodide concentration was investigated. Simulations were also performed using nominal reaction rate derived from in-situ ozone deposition measurements and using a preliminary representation of organic chemistry. Results show insensitivity of ambient ozone concentrations modelled by the chemical-enhanced scheme to oceanic iodide concentrations, and iodide reactions alone cannot account for observed deposition velocities. Consequently, we suggest a missing chemical sink due to reactions of ozone with organic matter at the air-sea interface. Ozone loss rates are estimated to be in the range of 0.5–6 ppb per day. A potentially significant ozone-driven flux of iodine to the atmosphere is estimated to be in the range of 2.5–500 M molec cm−2  s−1, leading to a mixing-layer enhancement of organo-iodine concentrations of 0.1–22.0 ppt, with an average increase in the N.E. Atlantic of around 4 ppt per day.